Elevated temperature may intensify the positive effects of nutrients on microbial decomposition in streams. (8th September 2014) - Fernandes, Isabel; Seena, Sahadevan; Pascoal, Cláudia; Cássio, Fernanda
Summary Climate change scenarios predict an increase in global temperature and alterations in precipitation regimes, which may change nutrient concentrations in waterbodies. In forested streams, decomposition of allochthonous organic matter is a key ecosystem process that is affected by the quality of plant litter entering the streams and several environmental factors, including nutrient concentrations, whose interactive effects are difficult to predict. We examined the concomitant effects of increased temperature, concentration of inorganic nutrients in stream water and litter quality on leaf decomposition and activity of microbial decomposers. Leaves of alder (Alnus glutinosa) and oak (Quercus robur), representative of high and low initial N content, respectively, were immersed in a stream (NW Portugal) to allow microbial colonisation and then were exposed in microcosms to increasing concentrations of N‐NO3 (0.09–5 mg L−1; six levels) and P‐PO4 (0.003–0.3 mg L−1; three levels) alone or in all possible combinations. One set of microcosms was kept at 12 °C, a temperature typically found in Iberian streams in autumn, and the other set at 18 °C to simulate a warming scenario. Nitrogen immobilisation was higher in alder than in oak leaves, and increased with temperature and N concentration in stream water for both leaf species. Leaf decomposition, fungal biomass accrual and reproduction were not affected by P concentration, but overall microbial activity increased asymptotically (Michaelis–Menten kinetics) with N concentration. Increased temperature led to an increase in maximum activity of fungal decomposers and to a decrease in N concentration needed to achieve it, especially in alder leaves. Under the predicted warming scenario, leaf decomposition may become faster in streams with lower nutrient levels, especially those receiving high‐quality leaf litter.